2011
DOI: 10.1111/j.1365-2710.2009.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a self-administration of medications programme on elderly inpatients’ competence to manage medications: a pilot study

Abstract: An inpatient SAMP improved elderly patients' ability to competently manage and adhere to their prescribed medications regimen. This finding needs to be confirmed in a larger controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 16 publications
(20 reference statements)
2
57
0
Order By: Relevance
“…However, once a medication routine is established, the older adults may be able to maintain it (Brown & Park, 2003). Lam et al (2011) also reported that patients became more competent with their medication self-management with time as they became familiar with their new medication regimens. Therefore, our findings emphasize the importance of interventions to improve medication use among older adults-especially during the first days after hospital discharge.…”
Section: Medication-related Problems After Hospital Dischargementioning
confidence: 94%
See 3 more Smart Citations
“…However, once a medication routine is established, the older adults may be able to maintain it (Brown & Park, 2003). Lam et al (2011) also reported that patients became more competent with their medication self-management with time as they became familiar with their new medication regimens. Therefore, our findings emphasize the importance of interventions to improve medication use among older adults-especially during the first days after hospital discharge.…”
Section: Medication-related Problems After Hospital Dischargementioning
confidence: 94%
“…Some studies have noted that there is a correlation between older age and increased medication-related problems (Beckman, Parker, & Thorslund, 2005;Cárdenas-Valladolid et al, 2010); however, this is not always the case (May et al, 2010;Roth & Ivey, 2005). Similarly, other select variables and medication-related problems have been shown to be related, such as gender (Barat et al, 2001;Beckman et al, 2005;Tordoff, Bagge, et al, 2010), educational background (Barat et al, 2001;Gray, Mahoney, & Blough, 2001;Rich, Gray, Beckham, Wittenberg, & Luther, 1996), living arrangement (Barat et al, 2001;Beckman et al, 2005;Lam et al, 2011), economic status (Haider, Johnell, Thorslund, & Fastbom, 2008;Stuart & Briesacher, 2002; The Ohio Department of Aging, The Aging Network, & The Ohio State University, 2007), vision (Beckman et al, 2005;Ferrario, 2008;Murray et al, 2004), hearing (Cárdenas-Valladolid et al, 2010;Ferrario, 2008;Murray et al, 2004), and depression (Barat et al, 2001;DiMatteo, Lepper, & Croghan, 2000;May et al, 2010).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…[4][5][6][7] Staff should embrace this policy to realise its benefits and promote patient autonomy wherever applicable. The initial investment on resources such as individual bedside cabinets and additional staff training in facilitating nurse administration can be offset by the long-term benefits to patients, reduction in prescribing errors and reduction in nurses' drug administration time.…”
Section: Self-administration Of Medicines By Inpatients: Are We Makinmentioning
confidence: 99%